2005
DOI: 10.1002/gcc.20277
|View full text |Cite
|
Sign up to set email alerts
|

Differential effect of epigenetic alterations and genomic deletions of CDK inhibitors [p16(INK4a), p15(INK4b), p14(ARF)] in mantle cell lymphoma

Abstract: Mantle cell lymphoma (MCL) is characterized by the chromosomal translocation t(11;14)(q13;q32), resulting in overexpression of CCND1 in the vast majority of cases. In addition, alterations of other cell-cycle-regulating signal pathways (CDKN2B/CDKN2A-CCND1 and ARF-MDM2-TP53) are frequently observed. However, the hierarchy of promoter methylations and genomic alterations as well as the interaction with other cell-cycle regulator CDKN1A is poorly understood. A complete methylation-specific PCR coupled with direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 19 publications
4
34
1
Order By: Relevance
“…There have been large differences in the reported proportions of patients with MCL having hypermethylated CDKN2B, from 9% 7 to 62% 6 despite the use of identical PCR primers. In the current study, CDKN2B was clearly hypermethylated compared with NBCs as assessed by both HELP analysis (P Ͻ .001) and mass spectrometry (P Ͻ .001), providing independent confirmation of CDKN2B promoter hypermethylation in most of the patients with MCL studied, consistent with the report by Hutter et al 6 Treatment of Z138 MCL cell line with DAC, SAHA, or both led to induction of HOXD8, PCDH8, and MLF1 expression and a reduction in cell viability. The combination of DAC and SAHA was synergistic, which could reflect multiple anti-MCL mechanisms: (1) reversing hypermethylation of tumor suppressor genes (supplemental Figure 3), (2) inhibition of HDAC1 (which was one of the hypomethylated and overexpressed genes identified), and (3) inhibition of CCND1 51 translation.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…There have been large differences in the reported proportions of patients with MCL having hypermethylated CDKN2B, from 9% 7 to 62% 6 despite the use of identical PCR primers. In the current study, CDKN2B was clearly hypermethylated compared with NBCs as assessed by both HELP analysis (P Ͻ .001) and mass spectrometry (P Ͻ .001), providing independent confirmation of CDKN2B promoter hypermethylation in most of the patients with MCL studied, consistent with the report by Hutter et al 6 Treatment of Z138 MCL cell line with DAC, SAHA, or both led to induction of HOXD8, PCDH8, and MLF1 expression and a reduction in cell viability. The combination of DAC and SAHA was synergistic, which could reflect multiple anti-MCL mechanisms: (1) reversing hypermethylation of tumor suppressor genes (supplemental Figure 3), (2) inhibition of HDAC1 (which was one of the hypomethylated and overexpressed genes identified), and (3) inhibition of CCND1 51 translation.…”
supporting
confidence: 91%
“…4 Epigenetic changes, such as methylation of gene promoters, have been shown to contribute to the pathogenesis of both solid and hematologic malignancies. 5 Single-locus studies analyzing methylation in MCL patient samples have shown hypermethylation of key genes, such as cell-cycle regulators p14 ARF and CDKN2A,6,7 protein phosphatase SHP-1 8 and Rho-adenosine triphosphatase PARG-1. 9 However these studies did not compare the methylation to NBCs, the normal counterparts of these malignant cells.…”
Section: Introductionmentioning
confidence: 99%
“…2 and 3). The previously described rare p16 (INK4a) promoter methylation may represent an additional mechanism of gene-specific cell cycle dysregulation in MCL [25]. 9p21 alterations were indirectly associated to other Fig.…”
Section: Discussionmentioning
confidence: 76%
“…Cyclin D1 overexpression or t(11;14)(q13;q32) translocation were identified by Northern blot analysis or cytogenetic FISH analysis, respectively. Genomic DNA was extracted from formalin fixed tumor tissue and/or buffy coat from leukemic samples as previously described [25]. After Ficoll separation of lymphocytes (buffy coat) and granulocytes (pellet), DNA was extracted applying the Nucleospin R Blood XL kit (Machery Nagel, Dueren, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation